2006
DOI: 10.1088/0957-4484/18/4/044032
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule transcription profiling with AFM

Abstract: Established techniques for global gene expression profiling, such as microarrays, face fundamental sensitivity constraints. Due to greatly increasing interest in examining minute samples from microdissected tissues, including single cells, unorthodox approaches, including molecular nanotechnologies, are being explored in this application. Here, we examine the use of single molecule, ordered restriction mapping, combined with AFM, to measure gene transcription levels from very low abundance samples. We frame th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 225 publications
(231 reference statements)
2
20
0
Order By: Relevance
“…While fragment distinction is beyond the scope of this paper, we analyze the feasibility of using a coding scheme to do this in [8] and we make this the center of our discussion in [34]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While fragment distinction is beyond the scope of this paper, we analyze the feasibility of using a coding scheme to do this in [8] and we make this the center of our discussion in [34]. …”
Section: Discussionmentioning
confidence: 99%
“…A natural choice is to use AFM to perform single-molecule analysis. Reed et al [8] developed such an analysis that classifies each mRNA by the following three steps: 1) synthesize a complementary DNA (cDNA) copy of each mature mRNA, 2) multiply cleave the cDNAs with a restriction enzyme, and 3) construct each cDNA classification label from ratios of the lengths of its resulting fragments. Thus, they showed the transcription profiling problem reduces to making high-precision measurements of cDNA backbone lengths—correct to within 20–25 bp (6–7.5 nm).…”
Section: Introductionmentioning
confidence: 99%
“…An another interesting use of coding theory and sequence detection application is in the use of cantilever probes for sequencing DNA [28].…”
Section: Cmentioning
confidence: 99%
“…Furthermore, recent work has shown that a combination of AFM imaging and manipulation allows for the precise and controlled manipulation of biological systems, from whole cells to the individual molecules [14][15][16][17][18][19][20][21][22][23][24], including DNA cutting and isolation [17,21,22], protein folding and unfolding [15,18], chromosomal dissection [14,15,19], single molecule's reaction [23,24], and single cell pushing, pulling, dragging and vibrating [16,20]. Our group has extended earlier work on the manipulation of single molecules of DNA by AFM [17], achieving positional isolation and biochemical analysis of single DNA molecules based on nanomanipulation and single-molecule PCR [22].…”
Section: Introductionmentioning
confidence: 99%